Understanding child neglect through selected works by Jacqueline Wilson - Toh, Florence Haw Ching; Liau, Agnes Wei Lin (International Journal of Children, Women, The Elderly and Persons with Disabilities, 2018)
Jacqueline Wilson is a former Children’s Laureate (2005-2007) whose contemporary realistic children’s novels have been translated into over 30 languages. Recognized as the most borrowed author in the British public libraries, Wilson uses her novels to highlight contemporary realistic issues and challenges which modern children are increasingly threatened with. Despite selling two million books a year, in-depth analyses into her works remain scarce. The paper attempts to fill the gap by reading three of her selected works. They are The Illustrated Mum (1999), Lola Rose (2003) and Lily Alone (2011). The discussion charts the struggles faced by the pre-adolescent girl protagonists who are repeatedly abandoned by their mothers. Consequently, the children live in a state of constant fear and uncertainty. The issue of child neglect discussed within these novels is significant because it corresponds to the worldwide concern pertaining to the increasing statistics of children victimized by parental neglect. Despite the numbers, it is believed that many more incidences occur unnoticed. Efforts to remedy the situation is therefore hampered by the lack of co-operation between victims and the authorities due to the sense of shame and embarrassment involved. Research has shown that children who are subjected to neglect are more likely to experience difficulties in their cognitive, emotional and behavioural development. The study is hence an important attempt to forward Wilson’s contemporary realistic children’s novels as useful tools to help young readers identify with and address the issue of child neglect prevalent within the nation. Key findings of the study encompass an understanding of how the pre-adolescent girl protagonists manage and overcome negligence. It is thereby hoped that the paper offers a viable alternative to expose and educate children on their right of protection, leading to a sense of empowerment as they learn to seek the necessary help when faced with similar encounters.